Behaviorally-Oriented Intensive Aphasia Program: Collaboration Leads to Optimal Outcomes - Fleming, Shawna; Clark, Brittany (Seminars in Speech and Language, 2022)
Aphasia is an acquired disorder affecting all language components across modalities. While common therapeutic approaches can result in some improvements, multiple studies establish that intensive therapeutic interventions are most effective; however, these approaches are not well defined. In addition, behaviorally-oriented approaches have been shown to be effective for other conditions, but have not yet been introduced to the treatment of aphasia. The purpose of the current study was to examine the efficacy of a novel, behaviorally-oriented, intensive communication intervention for aphasia (BICA) designed by a speech-language pathologist (second author) and a Board Certified Behavior Analyst (first author) for a 71-year-old woman with post–stroke aphasia. Using a case study design, the participant was provided with 12 hours/week of therapy for 12 weeks focusing on functional communication goals using a behavioral interpretation of language and stimulus control transfer procedures. The behavior analyst determined conceptually systematic interventions based on targets selected by the speech-language pathologist. The participant demonstrated substantial improvements in written language expression and comprehension, reading fluency, oral language expression, naming, and improved quality of life. Given the substantial gains the participant made in oral and written language post-stroke using the BICA therapy, further study is warranted.
Keywords: aphasia; collaboration; intensive; language; verbal behavior